2009
DOI: 10.1029/2008gl036627
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐annual relationships between polar ozone and the SAM

Abstract: [1] Observed co-variations between polar total column ozone and the Southern Hemisphere Annular Mode (SAM) during 1962 -2004 are presented and evaluated in a chemistry-climate model (CCM). Results show that austral spring total column ozone variability at South Pole is significantly related to the SAM, perhaps up to four months later; this relationship is only seen in simulations that include ozone depletion. The austral spring SAM also is linked to following late spring -early summer total column ozone over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 15 publications
5
33
0
Order By: Relevance
“…The strengthening SAM in the RCP8.5, in turn, may even itself modulate the ozone concentration. Positive phases of the SAM are often linked with decreasing ozone over the following several months (Fogt et al 2009b). Therefore, the increasing trend in the SAMI caused by GHGs may reduce the ozone concentration and is likely to reduce the impact of decreasing ozone-depleting substances on ozone recovery, which may impede the recovery.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The strengthening SAM in the RCP8.5, in turn, may even itself modulate the ozone concentration. Positive phases of the SAM are often linked with decreasing ozone over the following several months (Fogt et al 2009b). Therefore, the increasing trend in the SAMI caused by GHGs may reduce the ozone concentration and is likely to reduce the impact of decreasing ozone-depleting substances on ozone recovery, which may impede the recovery.…”
Section: Discussionmentioning
confidence: 97%
“…The project follows on from the previous CMIP3. However, whereas in CMIP3 ozone concentrations were usually fixed, in the CMIP5 models ozone is time dependent, an essential factor in accurately handling the temporal evolution of ozone destruction and recovery according to findings by Cai and Cowan (2007) and Fogt et al (2009a).…”
Section: A Modelsmentioning
confidence: 98%
See 1 more Smart Citation
“…A correlation between Antarctic stratospheric ozone depletion and the SAM index has been seen in observations Arblaster and Meehl, 2006;Wang et al, 2011; and references therein) and models (Perlwitz et al, 2008;Son et al, 2008;Thompson et al, 2011). The largest variability in the Antarctic stratosphere associated with the SAM signal is observed in the September-December period (Fogt et al, 2009). …”
Section: Proxy Data Setsmentioning
confidence: 99%
“…It can be observed that in the last years of when the polar vortex was stronger, the final breakdown takes place later than for years with a weaker one. Some studies have been done to analyse the potential factors contributing to the evolution of the Antarctic polar vortex and were in particular focused on the delay in its breakdown (Haigh and Roscoe, 2009;Fogt et al, 2009;Perlwitz et al, 2008;Gillett and Thompson, 2003). Their results have demonstrated that ozone depletion is a major factor influencing the delay in the polar vortex breakup, while the combined effects of solar activity, the phase of the quasi-biennial oscillation and greenhouse gases exert only a small influence.…”
Section: Ozone Variability In November and Decembermentioning
confidence: 99%